Chinese: problems of learning and teaching - Daulet, F. N. (Journal of Oriental Studies, 2016)
The article discussed the main problems of studying and teaching of Chinese language. Chinese language is presented from different perspectives: historical , typological , pragmatic and as an object of study and teaching . The paper highlights the problem of Chinese language teaching methodology , as well as their solutions are presented to . In the final part of the article presented “Practical Chinese course in 3 parts ,” developed by the author specifically for the students of higher educational institutions of the Republic of Kazakhstan.